Penerapan Desain Vector Pada Mural Di Dinding Kolam Renang Alas Outbound Edukasi Dusun Ngingas Desa Simpang - Muhammad Hasyim Ardiansyah; Aris Sutejo (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Mural is a visual art form that can give a unique identity and atmosphere to a space. This study aims to describe the process of applying vector design to the mural on the wall of the Alas Outbound Education swimming pool in Ngingas Hamlet, Simpang Village. The vector design was chosen because it gives a sharp and clean look, perfect for creating recognizable and attention-grabbing images. The application of vector design on murals in the Alas Outbound Education swimming pool is able to create a cheerful and educational atmosphere. Vector design provides image clarity, facilitates observation, and produces aesthetically pleasing works of art. This mural is expected to make a positive contribution to the experience of swimming pool visitors, as well as become a visual attraction that enriches the environment of Ngingas Hamlet.